Oscillation up to 1.92 THz in resonant tunneling diode by reduced conduction loss. (22nd January 2016) - Maekawa, Takeru; Kanaya, Hidetoshi; Suzuki, Safumi; Asada, Masahiro
Abstract: A large increase in oscillation frequency was achieved in resonant-tunneling-diode (RTD) terahertz oscillators by reducing the conduction loss. An n + -InGaAs layer under the air-bridge electrode connected to the RTD was observed to cause a large conduction loss for high-frequency current due to the skin effect. By introducing a new fabrication process removing the InGaAs layer, we obtained 1.92-THz oscillation, which extended the highest frequency of room-temperature electronic single oscillators. Theoretical calculations reasonably agreed with the experiment, and an oscillation above 2 THz is further expected with an improved structure of the slot antenna used as a resonator and radiator.